Internalizing Qur’anic Values through Tilawah Instruction: Implications for Students’ Learning Interest in an Indonesian Qur’anic Boarding School - Resti Julia; Oktari Kanus (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study investigated the Qur’anic values internalized through tilawah instruction, the pedagogical and institutional strategies used to cultivate them, and their perceived implications for students’ learning interest at Thariqul Jannah Qur’anic Boarding School, Indonesia. A descriptive qualitative field design was employed. Data were generated through in-depth interviews with 12 purposively selected participants—one administrator, one tilawah teacher, and ten students—supported by participant observation and institutional documentation. Data were analysed iteratively through reduction, thematic display, conclusion development, and verification. Trustworthiness was strengthened through source and method triangulation, member checking, persistent observation, and an audit trail. Three interconnected value dimensions emerged: i‘tiqādiyyah, comprising sincerity and gratitude; khuluqiyyah, encompassing humility, respectful attentiveness, and teacher role modelling; and ‘amaliyyah, reflected in trustworthiness, recitational accuracy, patience, and perseverance. These values were cultivated through talaqqi, halaqah, corrective feedback, habituation, emotional support, spiritual guidance, appreciation, home practice, and consistent educator modelling across transformation, transaction, and transinternalization stages. Students perceived these processes as supporting enjoyment, attention, curiosity, confidence, persistence, and active participation, although experiences varied and no causal effect was established. The study conceptualizes tilawah as a relational-spiritual pedagogy rather than merely technical or aesthetic recitation training and proposes a mechanism connecting value meaning, relational safety, competence-supporting feedback, and engagement. The findings extend research on Qur’anic education by explaining how values, pedagogy, institutional culture, and teacher–student relationships interact in a nonformal setting, offering a context-sensitive framework for designing holistic tilawah programs while avoiding unsupported claims of effectiveness for comparable Qur’anic learning institutions elsewhere.